Effect of Crack Patterns on the Stress Distribution of Hard Chromium Coatings under Sliding Contact: Stochastic Modeling Approach - Fochesatto, Nicolás Sebastián (2017)
In this work, the influence of different crack arrangements in the stress distribution of hard chromium (HC) coatings was determined. Three parameters for position and length of the cracks for two different types of coatings were probabilistically modeled based on measured scanning electron microscopy (SEM) images. Probability density functions (PDF) for those parameters were obtained to characterize each kind of coating. A two-dimensional finite element (FE) model of the coating in contact with a rigid disk was developed, modeling cracks with elliptical shapes. A Monte Carlo method was used to simulate different crack distributions for each kind of coating, and values of stress and strains in the domain were obtained. Both the J-integral and the stress intensity factors (SIFs) were taken as comparative parameters of the results. Coatings which statistically present larger quantities of shorter cracks have lower values of J-integral and SIFs, and, therefore, distribute stresses better than those with low density of longer cracks.